2008
DOI: 10.1051/vetres:2008042
|View full text |Cite
|
Sign up to set email alerts
|

Faecal shedding, alimentary clearance and intestinal spread of prions in hamsters fed with scrapie

Abstract: Shedding of prions via faeces may be involved in the transmission of contagious prion diseases. Here, we fed hamsters 10 mg of 263K scrapie brain homogenate and examined the faecal excretion of disease-associated prion protein (PrPTSE) during the course of infection. The intestinal fate of ingested PrPTSE was further investigated by monitoring the deposition of the protein in components of the gut wall using immunohistochemistry and paraffin-embedded tissue (PET) blotting. Western blotting of faecal extracts s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 56 publications
2
28
0
Order By: Relevance
“…An analogous study using lower doses of oral inoculum also demonstrated the fecal shedding of prions during clinical stages of disease by employing sPMCA amplification of prions in fecal extracts. 42 Importantly, these conclusions are also supported by the demonstration that mule deer incubating CWD after oral challenge did not yield prion infectivity within feces within the first 3-4 months after inoculation but feces contained infectivity after 9 months incubation through to clinical disease at 16 to 20 months. Using transgenic mouse bioassay, it was calculated that the levels of infectivity shed through feces over a 10 month period approached that present within a clinically infected whole brain.…”
Section: Secretion Of Prions Within Milkmentioning
confidence: 84%
See 1 more Smart Citation
“…An analogous study using lower doses of oral inoculum also demonstrated the fecal shedding of prions during clinical stages of disease by employing sPMCA amplification of prions in fecal extracts. 42 Importantly, these conclusions are also supported by the demonstration that mule deer incubating CWD after oral challenge did not yield prion infectivity within feces within the first 3-4 months after inoculation but feces contained infectivity after 9 months incubation through to clinical disease at 16 to 20 months. Using transgenic mouse bioassay, it was calculated that the levels of infectivity shed through feces over a 10 month period approached that present within a clinically infected whole brain.…”
Section: Secretion Of Prions Within Milkmentioning
confidence: 84%
“…[42][43][44] Accumulation of PrP Sc within the GALT may well lead to transit of the prion into the gut lumen and excretion within feces. Safar and colleagues used a rodent-scrapie model to demonstrate the presence of prions within feces.…”
Section: Excretion Of Prions Within Fecesmentioning
confidence: 99%
“…Deer, elk, moose, sheep, and cattle use their olfactory systems for reproductive, feeding, and exploratory purposes and thus frequently expose their NCs to environmental materials. There are a number of environmental sources of infectious prions, including decaying carcasses (34), placenta (35,36), antler velvet (37), blood (38)(39)(40)(41)(42), urine (43)(44)(45)(46), and feces (47)(48)(49)(50), that could be inhaled into the NC and horizontally transmit disease (7,8) in both captive and free-ranging animal populations. It is worth noting that soil-bound prions remain infectious (19,(51)(52)(53) and that the physical size of the intercellular spaces reported here would accommodate the particle size of silt and clay (between 2 and 50 m), allowing infection from inhaled contaminated soil.…”
Section: Discussionmentioning
confidence: 99%
“…Whether effects on prion infectivity mirror these observations is uncertain, as bovine ruminal and colonic microbiota preparations can degrade hamster 263K prion-derived PrP Sc , but prion infectivity is retained (Scherbel et al, 2006(Scherbel et al, , 2007. While the combined actions of host and microbiota-derived proteolytic enzymes may contribute to the partial digestion of certain prion isolates in the gut lumen, detectable levels of infectious prions can survive these processes and are secreted in the faeces of BSE-, CWD-and scrapie-infected hosts (Krüger et al, 2009;Maluquer de Motes et al, 2008;Safar et al, 2008;Tamgüney et al, 2009), and can survive passage through the gastrointestinal tracts of coyotes (Canis latrans) (Nichols et al, 2015) and crows (VerCauteren et al, 2012). One study has also proposed that bacterial components, such as LPS, may potentially enhance the abnormal folding of recombinant PrP (Saleem et al, 2014).…”
Section: Direct Effects Of the Gut Microbiota On Prionsmentioning
confidence: 99%